Pengaruh Profitabilitas, Leverage dan Firm Size terhadap Manajemen Laba pada Sub Sektor Food & Staples Retailing yang Terdaftar di BEI Periode 2018-2023 - Amelia Rahmawati; Immas Nurhayati; Denia Maulani (CV. ITTC INDONESIA, 2024)
This study aims to determine the effect of profitability, leverage and firm size on earnings management in food & staples retailing sub-sector companies listed on the IDX for the 2018-2023 period. This study uses a quantitative approach and uses secondary data sources taken from the company's annual financial statements in the food & staples retailing sub-sector for the 2018-2023 period. The data collection technique used in this study is to use documentation techniques and the sampling technique used in this study is purposive sampling method and the number of samples used is 4 companies in the food & staples retailing sub-sector with a research period of six years. The results showed that the profitability variable had a negative but significant effect on earnings management, the leverage variable had a negative but significant effect on earnings management and the firm size variable had no significant effect on earnings management. Meanwhile, the results of simultaneous research show that profitability, leverage and firm size variables affect earnings management.